Status gizi awal berdasarkan Patient Generated Subjective Global Assessment (PG-SGA) berhubungan dnegan asupan zat gizi dan perubahan berat badan pada penderita kanker rawat inap di RSUP Dr. Mohammad Hosein Palembang - Susetyowati Susetyowati; Yenita Yenita; Johan Kurnianda (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Weight loss is commonly detected among cancer patients in their early stages. This presumably happens due to low calory intake and increasing energy requirements which finally lead to malnutrition in cancer patients. Early detection to identify nutrition problems of cancer patients is through screening so as to maximize nutrient intake through nutrition therapy and diet modification and to improve nutrition status as well as quality of life of cancer patients.Objective: The study aimed to identify the relationship between nutrition status based on PS-SGA and nutrient intake and weight loss of cancer patients hospitalized at Dr. M. Hoesin Hospital of Palembang.Methods: The study was observational with prospective cohort study design. In this study the group that had fulfilled inclusion criteria were screened during their early hospitalization (within 24 hours) using patient-generated subjective global assessment score to identify their nutrition problem. Next, the group was divided into 2 smaller groups consisting of one group with malnutrition and another group without malnutrition. Analysis of nutrient intake obtained from foods provided by the hospital and outside the hospital was made to the two groups within 2 weeks of hospitalization using visual comstock and food record. Anthropometric measurement was made to find weight loss the subject of the study.Results: The results of the study showed that there was significant relationship between nutrition status and intake of energy and protein with p=0.000. The result of logistic regression test to nutrition status based on weight changes indicated that there was significant relationship between risk of nutrition and weight changes; patients with risk of nutrition had 7.016 times greater probability for weight loss than those without risk of nutrition (95% C5 2.896-16.997).Conclusion: There was significant relationship between nutrition status and nutrient intake among cancer patients and there was greater probability for weight loss.